PENDIDIKAN DI INDONESIA DAN NEGARA BERKEMBANG LAINNYA : SEBUAH STUDI KOMPARASI - Anna Widiastuti (Jurnal Dinamika Ekonomi & Bisnis, 2004)
Education system keeps changing till nowadays, not only in developed countries, but also in developing countries. Changing in education system involves tools and equipments used also. The implementation of high technology as equipments and tools in education is a need as the speed increased used of technology. There are so many human resources marked "professional and intellectual" as a result of the education process. In relation with this fact, has the education process already succeeded? How is the education system in Indonesia? Has it already succeeded as welt? This paper describes today's education system in Indonesia, by providing data and observing the problems.Keywords: Education system, problems in education, comparative studies in education.